2014
DOI: 10.1007/s00449-014-1284-4
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of seawater for cost-effective cultivation and harvesting of Scenedesmus obliquus

Abstract: Microalgae hold great promise as a source of biofuels and biochemicals. The main obstacles to their industrial application are the high cultivation and downstream costs related to media and harvesting. In the work, we explored the multiple potentials of seawater to address key issues relating to the cultivation of Scenedesmus obliquus. Seawater can sufficiently replace some of the key elements in BG11 medium such as MgSO4, CaCl2, and NaCO3, and its use can significantly reduce the quantity of water required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In seawater, the yellow-green colour is assumed that there is an indication of micro-algae growth by yellow-green algae (xanthophytes), which has chlorophyll E pigment [28]. Compared with freshwater, seawater contains more dissolved ions, the most abundant are sodium, chloride, magnesium, sulfate, and calcium, which are required for micro-algae to growth, including various minerals, such as nitrogen sources and phosphate sources [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In seawater, the yellow-green colour is assumed that there is an indication of micro-algae growth by yellow-green algae (xanthophytes), which has chlorophyll E pigment [28]. Compared with freshwater, seawater contains more dissolved ions, the most abundant are sodium, chloride, magnesium, sulfate, and calcium, which are required for micro-algae to growth, including various minerals, such as nitrogen sources and phosphate sources [29].…”
Section: Discussionmentioning
confidence: 99%
“…Five bottles with different water sources were put under the sun for 2 weeks. The water sources used in this experiment were mineral water (130), tap water (84), puddle (89), river (89), pool (91), aquarium (23), groundwater (4), rainwater (29), lake (4), reservoir (8), well (53), rice field (6), spring water (4), and ocean (1).…”
Section: Experimental Equipmentmentioning
confidence: 99%
“…Chlorella ellipsoidea (FBCC180008) and Scenedesmus dimorphus (FBCC110009), both acquired from the NNIBR (Nakdonggang National Institute of Biological Resources, Republic of Korea), were mixed in ten sets of cylindrical 10L plastic bottles for cultivation. SBG11 (10%-seawater-supplemented BG11) culture medium [33] with a constant 1%-CO2 (v/v)-enriched air flow (250 mL/min) at 28°C under continuous illumination at a light intensity of 100 µmol photons m -2 s -1 (LI-189 Li-Cor, PAR quantumsensor, Lincoln, USA) was used for strain maintenance. Preparatory to measurement of the microalgae's dry weight, the cells were filtered through filter paper (GF/C glass-fiber) and dried at a temperature of 60°C for 24 h, and subsequently, the filter paper's final weights were compared with the initial ones.…”
Section: -1-strains and Growth Mediummentioning
confidence: 99%
“…The addition of 20% deep-sea water to the culture medium effectively enhanced the cell growth and oil accumulation of the algae. Jung et al [ 9 ] found retardation in cell growth when more than 10% seawater was added to BG11 medium for cultivation of Scenedesmus obliquus , and higher fatty acid yields relative to those in the standard BG11. Some reports added NaCl to the medium to build a salt-stress environment for hyperaccumulation of lipids in limnetic algae, and the results were satisfactory [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the main nutrients, trace elements play an important role in rich algal growth, and are also costly. Fortunately, seawater contains abundant mineral elements supporting marine biology [ 9 ], which might also be used for freshwater algal activity. Therefore, cultivating freshwater microalgae with seawater has practical value and a good prospect for application.…”
Section: Introductionmentioning
confidence: 99%